La Pteridoflora del Parque Nacional Los Marmoles, Hidalgo, Mexico - Ramirez Cruz, S.=700 1 Sanchez Gonzalez, A.; Tejero Diez, D.
(Es, En)
ilus., 46 ref.
Keywords: PTERIDOPHYTA; HELECHOS; DISTRIBUCION GEOGRAFICA; COMPOSICION BOTANICA; TAXONOMIA; MEXICO; BOLETIN DE LA SOCIEDAD BOTANICA DE MEXICO